PENATALAKSANAAN FISIOTERAPI PADA KONDISI OSTEOARTHRITIS KNEE SINISTRA DISERTAI DIABETES MELLITUS TIPE II DENGAN MODALITAS TENS, EXERCISE THERAPY, DAN MULLIGAN TECHNIQUE - Syauqinaa Sabiilaa; Eko Budi Prasetyo (LPPM Universitas Pekalongan, 2018)
Diabetes Mellitus Type II is a disease of hyperglycemia due to the relative failure of β cells and insulin resistant. One of the complications of Diabetes Mellitus is a chronic musculoskeletal disorders, and the most is osteoarthritis of the knee, which is 53.3%. Osteoarthritis can be defined as a slowly progressive monoarticular disorder of unknown cause clearly. Osteoarthritis can cause physical disability in multiple levels, ie the level of impairment (joint damage, especially that caused complaints joints), the level of disability (the existence of a physical disability that disruption of activity of daily living), and functional limitation (limited ability of functional activity). In order to giving effective and efficient therapy, then conducted a certain phisiotherapy intervention and documentation. Intervention including all of phisiotherapy measurement that is an examination for pain by Visual Analogue Scale (VAS), muscle spasm by palpation, muscle strength by Manual Muscle Testing (MMT), range of motion by goniometer, and the ability of functional activity with Knee Injury Osteoarthritis Outcome Score (KOOS). In this case to contend the problems above may used modality sort of Transcutaneus Electrical Nerve Stimulation (TENS), Exercise Therapy, and Mulligan Technique.